OPEN DATA OPENS NEW DOORS. - THORESON, KAREN (Public Management (00333611), 2013)
The article discusses how access to government and corporate databases can promote development of new computer and mobile applications (apps). It mentions that open access to 249 datasets from 31 departments the city of San Francisco, California had resulted in the development of 53 apps by the city resident. It further states that Austin in Texas opened its departmental databases in 2011 and in 2012 organized its first hackathon, an event meant for computer programmers.